Long Non-coding RNA NEAT1 Alleviates Acute-on-Chronic Liver Failure Through Blocking TRAF6 Mediated Inflammatory Response - Xu, Yumin; Cao, Zhujun; Ding, Yezhou; Li, Ziqiang; Xiang, Xiaogang; Lai, Rongtao; Sheng, Zike; Liu, Yuhan; Cai, Wei; Hu, Ronggui; Wang, Hui; Xie, Qing (Frontiers in Physiology, 2019)
Background: Long noncoding RNAs (lncRNAs) have recently been tightly linked to plenty of human diseases. However, knowledge of acute-on-chronic liver failure (ACLF) related lncRNAs remains insufficient. In this work, we studied the role of the lncRNA NEAT1 in the pathogenesis of ACLF. Methods: ACLF model was established by challenging D-galactosamine (D-GalN)/lipopolysaccharide (LPS) i.p. in rats with cirrhosis. The serum levels of IL-1, IL-6 and HMGB1 were determined using ELISA. Quantitative real time-PCR and western blot were performed to evaluate RNA and protein levels of inflammatory response. RNA immunoprecipitation assay was performed to confirm protein that interacts with NEAT1. Findings: Over-expression of NEAT1 could interact with TRAF6 and decrease its ubiquitination level, and significantly reduced the expression levels of IL-6, IL-22. Importantly, in ACLF rat model, NEAT1 over-expression reduced several cytokines expression and alleviated the pathological status in contrast to the control group. Additionally, NEAT1 was increased and positively correlated with IL-22 and IL-6 levels in PBMCs from the ACLF patients. Interpretation: NEAT1 can suppress inflammatory response through blockade of TRAF6 ubiquitination in ACLF rat model, suggesting that lncRNA NEAT1 might play protective roles in the pathogenesis of ACLF and provide promising novel target for pharmacological intervention.